Harmonizing Humanity: Unraveling Javanese Moral Development Through Macapat - Tania, Basma; Prasetya, Anastacia Megawati; Hakim, Shaqilla Aulia; Chusniyah, Tutut; Pambudi, Kukuh Setyo (Ilomata International Journal of Social Science, 2024)
The Tembang Macapat, a Javanese literary tradition, intricately weaves together the journey of human growth and development—from the womb to our eventual return to the Divine. Each melodic stanza of the macapat resonates with a unique rhythm, mirroring the multifaceted nature of our existence. In this rich tapestry of Javanese culture, we find echoes of Lawrence Kohlberg’s three moral development stages: Pre-Conventional (focused on punishment and self-interest), Conventional (emphasizing social compliance and self-worth), and Post-Conventional (guided by social contracts and universal ethical principles). As humans evolve, they undergo profound transformations—a truth eloquently expressed in the tembang macapat. These verses serve as both a testament to our shared humanity and a call to personal excellence. Through their melodic wisdom, we aspire to become virtuous individuals who have fully blossomed. This paper delves into the exploration of Javanese moral development, anchored in the macapat, as seen through the lens of cultural enthusiasts in Malang. Employing a qualitative research approach with ethnographic methods, we unravel the intricate threads of morality woven into the very fabric of Javanese life.